Rediscovering the rare bromeliad Araeococcus goeldianus L.B. Smith (Bromelioideae) in Brazil and an amendment to its description - Pontes, Ricardo Ambrósio S. De; Versieux, Leonardo M. (Phytotaxa, 2018)
Araeococcus goeldianus L.B. Smith (1955) is endemic to the Guiana Shield (French Guiana and Brazil). It was described by specimens collected by J. Huber in 1895 in Amapá (Oiapoque, Vila Cunani), remaining undescribed for 60 years until its publication by Lyman B. Smith in 1955. The present work presents its rediscovery at the type locality, allowing us to extend its morphological characterization (floral structures, colors, measurements), presenting an amendment to the original description, besides information about habitat, conservation status (treated here as Vulnerable, D2), geographic distribution, photos of the species in its habitat, and structures under scanning electron microscopy.